A rede de serviços de atenção psicossocial na região sudeste da cidade de São Paulo: potencialidades e limites - Viega, Larri Padilha (2012)
The objective of this Master's thesis was to study the attention network of mental health care in the Southeast region of São Paulo. The study proposals have started from the author s everyday life and also from his inquiries while his work in healthcare area. The main objective was to identify the limitations and possibilities of public policy for mental health in that region, in view of the principles and national guidelines for the area and also on the parameters of the psychiatric reform. For this proposal, the guiding question was: What is the network configuration of territorial psychosocial care services in São Paulo? From this questioning, the potential, the contradictions and consequences for population health were investigated. The main conceptual categories used were: network, uninstitutionalization, care, mental health and others. This is a qualitative research that comprised literature, documentary and field researches, and also the observation of services dynamic, considering the work experience and the researcher s everyday as a Social Assistant in healthcare. We interviewed eight services which belong to the network of psychosocial care located in the catchment area of Southeast Health Coordination (three of them were from other jurisdictions). We interviewed eight users and eight professionals as a way of giving voice to the main subject in areas of care. In order to understand the meaning of the testimonies we used content analysis to identify the most important points for the study. As a result, the research shows that although the services have been rated very positively from the point of view of users, the relationship between them is very weak sets, showing that while public policy strategy, the network still requires improvement to their consolidation